2012
DOI: 10.4103/0253-7176.106022
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Double-Blind, Placebo-Controlled Study of Safety and Efficacy of a High-Concentration Full-Spectrum Extract of Ashwagandha Root in Reducing Stress and Anxiety in Adults

Abstract: Context:Stress is a state of mental or emotional strain or tension, which can lead to underperformance and adverse clinical conditions. Adaptogens are herbs that help in combating stress. Ayurvedic classical texts, animal studies and clinical studies describe Ashwagandha as a safe and effective adaptogen.Aims:The aim of the study was to evaluate the safety and efficacy of a high-concentration full-spectrum extract of Ashwagandha roots in reducing stress and anxiety and in improving the general well-being of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
134
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(183 citation statements)
references
References 10 publications
9
134
2
4
Order By: Relevance
“…Chandrasekhar et al 19 enrolled 64 participants in a 60-day clinical trial that compared 600 mg of WS per day with placebo. Significant differences were found for all outcome measures, including scores on the Perceived Stress Scale ( p < 0.0001), the General Health Questionnaire ( p < 0.0001), and levels of cortisol in the bloodstream ( p = 0.0006).…”
Section: Summary Of Trialsmentioning
confidence: 99%
“…Chandrasekhar et al 19 enrolled 64 participants in a 60-day clinical trial that compared 600 mg of WS per day with placebo. Significant differences were found for all outcome measures, including scores on the Perceived Stress Scale ( p < 0.0001), the General Health Questionnaire ( p < 0.0001), and levels of cortisol in the bloodstream ( p = 0.0006).…”
Section: Summary Of Trialsmentioning
confidence: 99%
“…The study demonstrated that KSM-66 Ashwagandha extract significantly decreased feelings of stress, depression, anxiety and significantly increased general well-being after 60 days based on three different extensively used sets of stress scales (p< 0.0001) (Chandrasekhar, Kapoor, & Anishetty, 2012). Also, there was a statistically significant decrease in serum cortisol levels after 60 days (p< 0.0006) (Chandrasekhar et al, 2012).…”
Section: Ashwagandhamentioning
confidence: 86%
“…Also, there was a statistically significant decrease in serum cortisol levels after 60 days (p< 0.0006) (Chandrasekhar et al, 2012). There were a few reports of adverse effects in both the placebo and the treatment group such as nausea, constipation, and drowsiness.…”
Section: Ashwagandhamentioning
confidence: 86%
See 1 more Smart Citation
“…For example, the adaptogen ashwagandha (Withania) significantly reduced stress in adults and significantly decreased serum cortisol levels after 60 days of treatment [24]. The reason for the lack of an effect of the adaptogen/vitamin product on cortisol levels after 28 days of treatment is not known.…”
Section: Discussionmentioning
confidence: 99%